Cyclic and Lasso Peptides: Sequence Determination, Topology Analysis, and Rotaxane Formation. (27th April 2018) - Elashal, Hader E.; Cohen, Ryan D.; Elashal, Heidi E.; Zong, Chuhan; Link, A. James; Raj, Monika
Abstract: A broadly applicable chemical cleavage methodology to facilitate MS/MS sequencing was developed for macrocyclic and lasso peptides, which hold promise as exciting new therapeutics. Existing methods such as Edman degradation, CNBr cleavage, and enzymatic digestion are either limited in scope or completely fail in cleavage of constrained nonribosomal peptides. Importantly, the new method was utilized for synthesizing a unique peptide‐based rotaxane (both cyclic and threaded) from the lasso peptide, benenodin‐1 ΔC5. Abstract : Schnittfestes Eiweiß : Makrocyclische und lassoförmige Peptide können mithilfe von positionsselektiver chemischer Spaltung und anschließender Tandem‐Massenspektrometrie‐Analyse sequenziert werden. Auf diesem Wege wurden zudem einzigartige Peptid‐Rotaxane (cyclisch und aufgefädelt) ausgehend von dem Lasso‐Peptid Benenodin‐1 ΔC5 synthetisiert.